Cerebral Mucormycosis: Navigating Fungal Intrusion, Immune Challenges and Vascular Consequences: A Multifaceted Case Report - Vangiliappan, Kannan; Raju, Nithya; Rajan, Redlin Jani; Kartik, Neesha Solanky (Indian Journal of Pharmacy Practice)
A 63-years-old male patient with a medical history of Hypothyroidism and T2DM, who had been irregularly adhering to his medication regimen, was admitted to a nearby hospital. He presented with complaints of altered sensorium and weakness on the left side of his body over the past three days and was subsequently diagnosed with a cerebrovascular accident, commonly known as a stroke. Notably, his recent medical records indicated a total loss of vision and double vision. This prior episode had been attributed to invasive Fungal Sinusitis, for which he had received treatment with Inj. Liposomal Amphotericin B. Upon physical examination, the patient was found to be drowsy and unresponsive. Laboratory investigations revealed abnormalities in WBC, Leucocyte levels, Neutrophil and Lymphocyte counts, as well as random blood glucose levels. Imaging studies confirmed the diagnosis of a CVA. In response to his condition, the patient underwent a comprehensive treatment regimen, which included the administration of Glucocorticoids, lipid-lowering medications, antibiotics, oral hypoglycaemic agents, and vitamin supplements. Following the course of treatment, the patient's condition stabilized, and he was eventually discharged from the hospital. During his discharge, he received thorough counselling regarding the importance of adhering to his medication regimen. This case emphasizes the difficulties in treating cerebral mucormycosis in a patient with a history of chronic alcoholism, smoking, Type 2 Diabetes Mellitus, and hypothyroidism. Promptly recognizing and treating Cerebral mucormycosis, while also addressing underlying health condition like CVA, UTI, electrolyte imbalance and Drug induced Hyperthyroidism are crucial for improving patient outcomes.
Keywords: Fungal sinusitis; Liposomal Amphotericin-B; Cerebralmucormycosis; Cerebrovascular Accident; Adverse Drug Reaction; Hyponatremia; Hypocalcaemia; Hypokalaemia